Urinary metabolites of furan in waterpipe tobacco smokers compared to non-smokers in home settings in the US. (15th October 2020) - Kassem, Nada O.F.; Peterson, Lisa A.; Liles, Sandy; Kassem, Noura O.; Zaki, Flora K.; Lui, Kung-Jong; Vevang, Karin R.; Dodder, Nathan G.; Hoh, Eunha; Hovell, Melbourne F.
Highlights: Furan metabolite, NAC-BDA-NAL was higher in WPT smokers compared to non-smokers. Furan metabolite, NAC-BDA-Lys sulfoxide was higher in WPT smokers compared to non-smokers. Urinary cotinine levels increased significantly 26.1 times post smoking WPT. Abstract: Objectives: Determine uptake of furan, a potential human carcinogen, in waterpipe tobacco (WPT) smokers in home settings. Methods: We analysed data from a US convenience sample of 50 exclusive WPT smokers, mean age 25.3 years, and 25 non-smokers, mean age 25.5 years. For WPT smokers, data were collected at a home visit by research assistants during which participants smoked one WPT head of one brand for a mean of 33.1 min in their homes. Research assistants provided and prepared a WP for participants by weighing and loading 10 g of WPT in the WP head. At the completion of the smoking session, research assistants measured the remaining WPT. Cotinine and six furan metabolites were quantified in first morning urine samples provided on 2 consecutive days for non-smokers, and on the morning of a WPT smoking session and on the following morning for smokers. Results: WPT smokers consumed a mean of 2.99 g WPT. In WPT smokers, urinary cotinine levels increased significantly 26.1 times the following morning; however, urinary metabolites of furan did not increase significantly. Compared to non-smokers, 2 furan metabolites, N-acetyl-S-[1-(5-acetylamino-5-carboxylpentyl)-1H-pyrrol-3-yl]-L-cysteine and N-acetyl-S-[1-(5-amino-5-carboxypentyl)-1H-pyrrol-3-yl]-L-cysteine sulfoxide, were significantly higher in WPT smokers in pre and in post WPT smoking levels. Conclusions: To enable a more rigorous assessment of furan exposure from WPT smoking, future research should determine furan concentrations in WPT smoke, quantify furan metabolites from users of various WPT brands; and extend the investigation to social settings where WPT smoking is habitually practiced.